Factores de virulencia y métodos de diagnóstico laboratorial de Candida auris causante de infecciones nosocomiales. Revisión sistemática - Mejía Vega, Guissela Sthefanía (2024)
Nosocomial infections are those that develop 48 hours after the patient's admission to a hospital and can be caused by various microorganisms such as fungi and bacteria, it is particularly dangerous due to antimicrobial resistance. A microorganism of great clinical relevance is Candida auris, it is an emerging pathogenic yeast that has been identified as a cause of hospital infections. The purpose of this study is to describe the main virulence factors of C. auris. and indicate the laboratory methods used for the identification of this pathogen. To this end, a systematic review has been executed in the PubMed, Scopus and SciELO databases, following the guidelines of the Cochrane system. We applied the PRISMA method for screening; for which, we selected publications starting from 2013 and excluding the grey literature. 17 studies have been included in the systematic review which were evaluated through the JBI tool, evidencing a risk of bias ranging from moderate to low. Six studies have been found indicating that the main virulence factors are resistance to antifungals, adhesion and biofilm formation; enzymatic activity; evasion of the immune system; thermotolerance and halotolerance. Also, eleven studies detailed the main diagnostic methods of which they considered that CHROMagar™ Candida Plus is useful in 66%, MALDI-TOF VITEK-MS® in 17%, and real-time PCR has a diagnostic utility of 50%. In short, C. auris. is an emerging fungus notable for its resistance to multiple antifungals and its ability to cause serious infections, especially in hospital settings. Timely identification and treatment are crucial to prevent outbreaks and reduce associated mortality